KEPENTINGAN KOTA PADANG DALAM MEMBINA KERJASAMA SISTER CITY DENGAN KOTA HILDESHEIM - Kardi, Hasbi; Yealta, Den (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
Diplomatic relations are a cooperative relationship carried out by each country in this era of globalization. Currently, it is not only countries that are able to establish diplomatic relations but region/city can also establish diplomatic relations with other regions/cities that are inside of a foreign country. This is done to gain profit and achieve the national interests of a region or city. One form of diplomatic cooperation between regions is a sister city, also often called a twin city. The city of Padang and the city of Hildesheim is one example of cooperation between two cities. The city of Padang has established sister city cooperation with Hildesheim since 1988 until now in various sectors in order to achieve the national interests of the city of Padang. In this study, researchers will examine the reasons in which why the city of Padang cooperates with the city of Hildesheim and examine the national interests of Padang that has been achieved through the cooperation of sister cities of Padang and Hildesheim. This research was conducted using qualitative, data collectiing methods, and library research where researcher collects data and information through in-depth understanding of books, journals, articles, and other sources of information that are relevant to this research. The conclusion that the researcher was able to conclude in this study is that the sister city cooperation that has existed for 34 years has not given many significant results, the communication between the two parties has not been intensively carried out. This had also caused the vacancy of the cooperative relations between the city of Padang and Hildesheim in 2006. Then, in 2012 the sister city cooperation was re-established with the revitalization of the MoU which focused more on culture and empowering human resources. However, even after carrying out the revitalization, the results of this cooperatoin have not yet been clearly seen. Even so, through several cooperation programs at the beginning of the sister city coooperation, some of the national interests of the city of Padang was able to be materialized, such as in the fields of engineering and infrastructure, as well as social and culture. Keywords : cooperation, sister city, Padang, Hildesheim, Paradiplomcy.